2013
DOI: 10.1186/1757-1146-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Training the next generation of clinical researchers: evaluation of a graduate podiatrist research internship in rheumatology

Abstract: BackgroundThe aim of this study was to evaluate the effectiveness of the Arthritis Research UK funded graduate internship scheme for podiatrists and to explore the experiences of interns and mentors.MethodsNine new graduates completed the internship programme (July 2006–June 2010); six interns and two mentors participated in this study. The study was conducted in three phases. Phase 1: quantitative survey of career and research outcomes for interns. Phase 2 and 3: qualitative asynchronous interviews through em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…This in turn fosters evidence‐based practice and helps facilitate the nurse and AHP MSK researchers of the future. This model has the potential to be transferable across health disciplines to enable more early‐career clinicians to become research active (Naidoo, Bowen, Arden, & Redmond, ).…”
Section: Resultsmentioning
confidence: 99%
“…This in turn fosters evidence‐based practice and helps facilitate the nurse and AHP MSK researchers of the future. This model has the potential to be transferable across health disciplines to enable more early‐career clinicians to become research active (Naidoo, Bowen, Arden, & Redmond, ).…”
Section: Resultsmentioning
confidence: 99%
“…Clough et al [17] reported that supporting early career clinical and research training through fellowships increased the likelihood of securing externally funded doctoral training awards with many fellowship-holders moving into academic roles. Naidoo et al [15] similarly found in their evaluation of a graduate podiatry internship (which was the forerunner of the 2015 -18 programme), that the programme was valuable to the interns' careers and supported research capacity building in foot and ankle rheumatology. They also identi ed the importance of mentors and peer support, and the impact the internship had on changing perceptions of research [15].…”
Section: Discussionmentioning
confidence: 99%
“…Naidoo et al [15] similarly found in their evaluation of a graduate podiatry internship (which was the forerunner of the 2015 -18 programme), that the programme was valuable to the interns' careers and supported research capacity building in foot and ankle rheumatology. They also identi ed the importance of mentors and peer support, and the impact the internship had on changing perceptions of research [15]. More broadly, our evaluation re ects the core principles for research capacity building identi ed in the wider internship literature, namely the importance of developing skills and con dence, fostering partnerships and collaborations, and valuing research for excellence [3,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations